2013
DOI: 10.1515/jpem-2012-0297
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal aorta intima media thickness in obese children

Abstract: The aim of this study is to investigate whether abdominal aorta intima media thickness (aIMT), increases in obese children and to determine risk factors. Ninety-six children aged 5-16 (51 obese and 45 non-obese) were enrolled in this prospective and cross-sectional study. Age, gender, and relative body mass index (BMI) were recorded. Their serum lipids, thyrotropin, fasting glucose and insulin levels were analyzed. The homeostasis model assessment (HOMA-IR) score was calculated for insulin resistance. Anthropo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The time of the development of aortic abnormalities and their relationships to comorbidities are poorly understood. Screening aaIMT by ultrasound as a noninvasive method can give us an opportunity for the early assessment of cardiac risk in obese children [18]. Yücel et al [18] reported a positive correlation between aaIMT and age, SBP, HOMA-IR, DBP and fasting glucose values in obese children.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The time of the development of aortic abnormalities and their relationships to comorbidities are poorly understood. Screening aaIMT by ultrasound as a noninvasive method can give us an opportunity for the early assessment of cardiac risk in obese children [18]. Yücel et al [18] reported a positive correlation between aaIMT and age, SBP, HOMA-IR, DBP and fasting glucose values in obese children.…”
Section: Discussionmentioning
confidence: 99%
“…Screening aaIMT by ultrasound as a noninvasive method can give us an opportunity for the early assessment of cardiac risk in obese children [18]. Yücel et al [18] reported a positive correlation between aaIMT and age, SBP, HOMA-IR, DBP and fasting glucose values in obese children. Further, they found BMI as an independent risk factor for an increased aaIMT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation